Accessibility of COVID-19 Vaccines in African Countries: A System Dynamics Model Examining Income, Logistics, and Governance - Oya Öztürk; Muhammed Çelik (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
To combat the COVID-19 pandemic, pharmaceutical companies, biotech companies, national governments, and universities have jointly developed a variety of vaccines. After this stage, widespread and effective vaccination on a global scale has become the most crucial aspect in the fight against the pandemic. The discovery of vaccines has brought up the issue of how to deliver them quickly and fairly to those living in underdeveloped countries. Vaccination encompasses not only the medical aspect but also the concepts of accessibility, availability, equitable, fair, and rapid distribution as a whole. The main theme of our study is to comparatively highlight the impact of factors other than the medical aspect of vaccination on vaccination, specifically within the context of the African continent. African countries particularly have faced the most problems in accessing and distributing vaccines. This study aims to identify the barriers to the delivery of the Covid-19 vaccine to African countries. In this study, we analyzed the vaccine supply, governance index, and logistics infrastructure factors affecting access to vaccines in the context of various scenarios, using the system dynamics method. The findings of this study show that income level is the most significant variable. Additionally, improving logistics performance and infrastructure and governance index increase more equitable access to vaccines in African countries.